Implementation of a Clinical Practice Guideline for the Management of Tumor Lysis Syndrome at a Tertiary Care Hospital: A Retrospective Cohort Study - Raed Hamed Alharbi; Salman Ali Alabdali; Buthainah B. Alammash; Shalam Mohamed Hussain; Ahmed Abdulrahman Alsubhi; Hossein M. Elbadawy; Alaa Ibrahim Alrais (Hail Journal of Health Sciences)
Background: Tumor lysis syndrome (TLS) is a metabolic disorder occurring in cancer patients, often triggered by chemotherapy. It involves the rapid release of cellular contents into the bloodstream, causing electrolyte imbalances and metabolic disturbances. TLS can lead to severe complications such as acute renal failure and arrhythmias. Management relies on hydration and the use of allopurinol and rasburicase. Methods: This is a retrospective, single-center cohort study. Patients who had high uric acid results (>476 μmol/L) were allocated in the health records system. All eligible patients were allocated to either the “as per proposed guidelines” group, or the off proposed guideline group if they were treated otherwise. Uric acid normalization after 3, 5, and 7 days was observed. Results: Out of 59 patients, 38 (64.5%) were male and 21 (35%) were female. The rate of compliance with respect to the proposed institutional TLS guideline was very poor as 95% of the cases did not fully comply with the proposed guidelines for uric acid normalization for patients treated “as per” the proposed guideline on day 3 after initiation of treatment were for three patients. For patients treated “off” the guidelines, uric acid normalization was achieved after 3 days in 7 patients, after 5 days in 7 patients, and after 7 days in 42 patients. Conclusion: This study highlights the challenges in implementing clinical practice guidelines for the management of TLS. The rate of compliance showed a lack of adherence to the guidelines resulting in delays in achieving uric acid normalization. These findings underscore the dire need for ongoing education and training initiatives to improve health-care provider adherence to established guidelines and optimize the patient outcomes in TLS management.